Thermal pyrolysis of LDPE/PP multilayer and metalized BOPP plastic packaging to optimize oil/wax yield for use as a fuel source - Madyibi, Salizwa Siliziwe (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.